Oil palm productivity remains limited as price of cooking oil soars in Indonesia - Nisrina Nuraini Nafisah; Felippa Amanta (Center for Indonesian Policy Studies (CIPS), 2022)
The high price of cooking oil in Indonesia has been under the spotlight from the fourth quarter of 2021 up to the beginning of 2022. Between March and December 2021, Index BU RT 1 recorded a 56% price increase that peaked at IDR 20,667/liter in December. Although the price of cooking oil has since gone down to IDR 19,555/liter by January 2022, it remained expensive as it was still 46.2% higher than the price in January 2021.
Keywords: 330